Rapid and sensitive on‐site genetic diagnostics of pest fruit flies using CRISPR‐Cas12a. Issue 1 (22nd September 2022) - Alon, Dan Mark; Partosh, Tamir; Burstein, David; Pines, Gur
Abstract: BACKGROUND: Bactrocera zonata, a major fruit pest species, is gradually spreading west from its native habitat in East Asia. In recent years it has become a significant threat to the Mediterranean area, with the potential of invading Europe, the Americas, and Australia. To prevent it spreading, monitoring efforts in cultivation sites and border controls are carried out. Despite these efforts, and due to morphological similarities between B. zonata and other pests in relevant developmental stages, the monitoring process is challenging, time‐consuming, and requires external assistance from professional laboratories. CRISPR‐Cas12a genetic diagnostics has been rapidly developing in recent years and provides an efficient tool for the genetic identification of pathogens, viruses, and other genetic targets. Here we design a CRISPR‐Cas12a detection assay that differentially detects two major pest species, B. zonata and Ceratitis capitata. RESULTS: We demonstrate the specificity and high sensitivity of this method. Identification of target pests was done using specific and universal primers on pooled samples, enabling differentiation of pests with high certainty. We also demonstrate reaction stability over time for future on‐site applications. DISCUSSION: Our easy‐to‐use and affordable assay employs a simple DNA extraction technique together with isothermal amplification and Cas12a‐based detection. This method is highly modular, and the presented target design method can be applied to a wide array of pests. This approach can be easily adapted to fit local threats and requires minimal training of operators in border controls and other relevant locations, reshaping pest control and making state‐of‐the‐art technologies available worldwide, including in developing countries. © 2022 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Pest identification can be very challenging at certain developmental stages, creating a major bottleneck in the trafficking of agricultural goods worldwide. Using isothermal amplification and CRISPR‐Cas12a, we developed a fast, easy‐to‐use, and sensitive method for on‐site genetic differentiation of two major pests, Bactrocera zonata and Ceratitis capitata.